Trauma in Natsume Soseki's Kokoro: A character analysis - Fadhli Ruhman; Safrina Noorman; Nia Nafisah (Universitas Pendidikan Indonesia (UPI), 2020)
Trauma, meaning wound, is a common phenomenon in our modern world and this phenomenon is represented in many works of literature in various ways. One of the examples of literary work that attempts to represent trauma is Natsume Soseki’s Kokoro, a 1914 Japanese novel written by one of the most famous Japanese author. This research aims to answer the question of how trauma shape a person’s identity in the translated version of Natsume Soseki’s Kokoro (1957). This research focuses on the character development of one of the main character in the story, Sensei. Employing Caruth’s (1995) trauma theory as a the theoretical framework, this study uses descriptive qualitative as the approach. The result finds that Sensei’s identity is shaped by two major traumatic event in his life, the betrayal of his uncle and the death of his close friend. In response to the two tragic events, Sensei constructs an identity that are characterized by attributing cynical attitude, attaching guilt, and casting fear. Because he feels he is haunted by his trauma, he decided to commit suicide in order to be free. The way Sensei constructs his identity in response to his traumatic past is also a reflection of a postmodern notion identity in which a person’s identity is never absolute and is prone to change.Keywords: Identity, trauma, Japanese literature.